Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

We are given $R(t)$ = $P(X>t)$ for all $x > 0$ and

$$R(0) = 1 - Fx(0) = 1\text{ and }\lim\limits_{t \to \infty} R(t) = 0$$

The random variable $X$ also satisfies the memoryless property:

$$P(X>s+t|X>t) = P(X>s)\text{ for }s>0\text{ and }t>0$$

Let $R'(0) = - \lambda\ where \ \lambda\ ,$ is some positive constant. I need to show that X must be exponentially distributed.

Given that $\dfrac{R(t + h) - R(t)}{h}$ = $R(t)\left[\dfrac{R(h) - 1}{h}\right]$

Show that by letting $\lim\limits_{h\to \infty}$ $\dfrac{dR(t)}{dt} = -\lambda$$R(t)$ (I think we should use Hopital's rule here I am not sure by differentiating $\left[\dfrac{R(h) - 1}{h}\right]$ and letting $h$ tend to $0$, we will get $-\lambda$ for this part but I got stuck afterwards).

Also argue that $X$ is an exponential random variable with rate parameter $\lambda$ by solving the differential equation above respecting the conditions:

$$R(0) = 1 - Fx(0) = 1\text{ and }\lim\limits_{t \to \infty} R(t) = 0$$

share|cite|improve this question
Using the definition of conditional probability, the memoryless property can be re-written as $$P\{X > s+t\} = P\{X>s\}P\{X>t\} \Rightarrow R(s+t)=R(s)R(t).$$ Many calculus texts show that a continuous function $R(t)$ with this property must be of the form $a^t$ for some $a$, or identically $0$. Maybe you can adapt their proofs to your homework problem. – Dilip Sarwate Feb 8 '12 at 15:31
Hi @Dilip Sarwate, one of the questions was actually to prove that property. Which I did. So now I'm left with these two questions. – Alistair Feb 8 '12 at 15:32
$R(0) = a^0 = 1$. $R'(0) = \left.\frac{d}{dt}a^t\right|_{t=0} = -\lambda$. I always have to look up the derivative of $a^t$ with respect to $t$ but if I pulled down the book off my shelf, I suspect I would find that $\ln a = -\lambda$ and so $a = e^{-\lambda}$, and so $R(t) = e^{-\lambda t}$ or maybe not.... – Dilip Sarwate Feb 8 '12 at 15:41
@DilipSarwate, the thing is we are trying to prove that this is an exponential distribution, for the first part I believe by using l'hopital's rule, with limit of h tending to 0 and differentiating the part in brackets we will get $[\dfrac{R'(0)}{1}]$ which would equal -$\lambda$ – Alistair Feb 8 '12 at 15:45
Please read my comment on your Failure time distribution question where you said all this was not homework. Once you prove that $$R(t) = P\{X > t\} = 1 - F(t) = \exp(-\lambda t),$$ for which I more or less gave you a complete proof above, all that remains to be done is show that $$f(t) = \frac{d}{dt}F(t) = -\frac{d}{dt}R(t) = \lambda\exp(-\lambda t)\mathbf 1_{(0,\infty)}$$ and claim that $X$ is an exponential random variable with parameter $\lambda$. – Dilip Sarwate Feb 8 '12 at 16:01
up vote 2 down vote accepted

Below is the standard argument, which is undoubtedly done in essentially the same way in your textbook. After a small amount of probability, the rest is just calculus. We are told that $$P(X>s+t\,|\,X>t) = P(X>s). \qquad\qquad(\ast)$$ Let $A$ be the event $X>s+t$, and let $B$ be the event $X>t$. We know that $$P(A\,|\,B)=\frac{P(A\cap B)}{P(B)}.$$ In this case, $P(A\cap B)=P(A)$. So
$$P(X>s+t\,|\,X>t) = \frac{P(X>s+t)}{P(X>t)}.$$ Using $(\ast)$, we conclude that $$\frac{P(X>s+t)}{P(X>t)}=P(X>s).$$ This may be more compactly rewritten as $$R(s+t)=R(s)R(t).$$ Precisely this equation was given in a comment by Dilip Sarwate.

To put you on more familiar ground, we replace $s$ by $x$, and $t$ with $h$. So we have reached the equation $$R(x+h)=R(x)R(h).\qquad\qquad(\ast\ast)$$ Subtract $R(x)$ from both sides, and then divide by $h$. We arrive at $$\frac{R(x+h)-R(x)}{h}=R(x)\frac{R(h)-1}{h}.$$ Let $h$ approach $0$. As $h$ approaches $0$, the right-hand side, by definition, approaches $R'(0)$, which we were told is $-\lambda$. So the left-hand side has a limit, which by definition is $R'(x)$. (By only considering positive $h$ only, we are being a little dishonest. Don't worry about it too much.)

So after some calculation, we have reached the differential equation $$R'(x)=-\lambda R(x), \quad\text{or if you prefer}\quad\frac{dR}{dx}=-\lambda R.$$ This is the familiar differential equation for exponential decay. The general solution is $$R(x)=R(0)e^{-\lambda x}.$$ We were told that $R(0)=1$. It follows that $R(x)=e^{-\lambda x}$.

So the cumulative distribution function $F_X(x)$ of the random variable $X$ is $1-e^{-\lambda x}$ (for $x>0$). Differentiate with respect to $x$. We conclude that the probability density function $f_X(x)$ of $X$ is $\lambda e^{-\lambda x}$ (for $x>0$).

share|cite|improve this answer
exponential decay, that's what I was looking for. Thanks! – Alistair Feb 8 '12 at 20:32

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.